Perbandingan Estimasi Radar Cuaca Dopler Baron Terhadap Data Observasi Kejadian Hujan Di Kota Kupang - Ni Putu Nonik Prianti; Roddialek Pollo; Judi K. Nasjoro; Sulton Kharisma (Bumi Lestari Journal of Environment, 2020)
Radar is able to provide information about extreme weather observations in the form of heavy rain, so it is important to find the level of accuracy of the radar in providing extreme weather information. So that with accurate data disaster mitigation can be done by creating an early warning system using radar data in order to minimize the impact that will occur. Comparative analysis of the estimated rainfall events on the radar with surface observation data shows a good level of accuracy, but the blankness of the data on the radar due to damage thus influences the decision making of the forecasters when providing extreme weather information quickly to the public. By knowing the radar accuracy level is quite good in estimating rain events, BMKG can provide weather information in the form of appropriate early warning so that people can anticipate extreme weather events